SYNTHESIZED OF SULFONATED POLYANILINE (SPAN) AND ITS APPLICATION AS COUNTER ELECTRODE IN DYE SENSITIZED SOLAR CELL (DSSC) - NURFALAH (NIM: 20514004), FAUZIAH
Dye Sensitized Solar Cells (DSSC) is one of semiconductor-based solar cell using a photoelectrochemical phenomenon as the basic principle for generating electrical energy. The DSSC components consists of photoanode, dye, electrolyte, and counter electrode. Counter electrode of DSSC requires high electrocatalytic activity to reduce I3 - ions from the electrolyte. The counter electrode which has been used is a conductive glass coated with platinum (Pt). Pt has a high conductivity and good electrocatalytic activity but the expensive price of Pt caused very high of DSSC manufacturing cost. The alternative materials had been needed to replace high cost Pt. Conductive polymers such as polyaniline (PANI) and its derivatives was reported to be applied as counter electrode to replace the metal electrodes in the DSSC system. PANI has several advantages characteristics compared to other conductive polymers, such as a high stability, economical production costs, electronic conductivity can be changed reversibly with oxidation or reduction reaction, so that PANI was often researched at the rapid application development. However, PANI was more difficult to processed because it was not soluble in common solvents such as water and methanol which led to many studies on the modification of PANI. One of the interesting modification of PANI is sulfonated polyaniline (SPAN), with inserting sulfonate group (-SO3-) into the aniline ring. SPAN has better properties than PANI because it can make an ohmic contact with the metal, it has a good electrocatalytic activity, and it is soluble in common solvents such as water and methanol. The purpose of this study is SPAN synthesis, which it was derived from PANI. SPAN will be applied at solar cells through DSSC fabrication which includes preparation photoanode, dye, an electrolyte solution, and the counter electrode where SPAN is used in this part. In its application, SPAN is mixed with carbon-based materials such as graphite and activated carbon. Graphite is used because it has a high electrical conductivity and activated carbon is used because it has a good electrocatalytic activity. The conductivity values of SPAN was measured with LCR Meter and it was characterized with FTIR spectroscopy and Raman spectroscopy. DSSC devices were characterized using solar simulator Oriel S013A and V-I Keithley 2400. SPAN has a conductivity value of 4.5 x 10-3 S/cm at 50 Hz. The presence of sulfonate group in PANI chain is indicated by the appearance of the peak at wave number 1020 cm-1 indicating stretching vibration of S=O group and the peak at wave number 1068 cm-1 indicating stretching vibration of C-S group. Raman